A comparatively optimization of dosages of oxidation agents based on volatile solids and dry solids content in dewatering of sewage sludge. (1st December 2017) - Yu, Wenbo; Yang, Jiakuan; Tao, Shuangyi; Shi, Yafei; Yu, Jiangwei; Lv, Yang; Liang, Sha; Xiao, Keke; Liu, Bingchuan; Hou, Huijie; Hu, Jingping; Wu, Xu
Abstract: Organic content of sludge is a major factor influencing its dewaterability. Conditioning sewage sludge with oxidation reagents (Fenton's reagent or Fe 2+ /persulfate) can effectively improve sludge dewaterability. In traditional conditioning process of sewage sludge, the optimization of conditioner dosage were commonly based on volume of sludge (referred as mg/L) or mass of dry solid (DS) of sludge (referred as mg/g DS). However, inconsistency of the oxidation dose mode existed for different sewage sludge sources. In this study, sludge samples of different volatile solids (VS) contents were used to derive optimal dosages of Fenton's reagent and Fe 2+ /persulfate, using the response surface methodology (RSM). For the case of Fenton's reagent, the optimal dosages of Fe 2+ and H2 O2 were 107–110 mg/g VS and 86–88 mg/g VS, respectively. For Fe 2+ /persulfate, the optimal dosages of Fe 2+ and persulfate were 49 mg/g VS and 269–271 mg/g VS, respectively. The optimal dosages of the oxidation reagents based on VS contents were proved to be consistent and effective for different sewage sludge with different organic matter contents from different wastewater treatment plants (WWTPs). In contrast, the optimal dosages of oxidation reagents, based on DS, fluctuated significantly for different sludge sources. Furthermore, sewage sludge dewaterability was significantly related to the degradation and the content of loosely bound extracellular polymeric substances (LB-EPS) in the organic matters of conditioned sludge ( R 2 > 0.9, p < 0.01). Thus, the improvement of sludge dewaterability could be related with the destruction of the VS in sludge with the conditioners of oxidant reagent. It indicated that optimization of oxidation reagent based on VS content is more plausible than that of based on DS content for different sewage sludge with different organic matter contents. Graphical abstract: Image 1 Highlights: Oxidant reagent dosage was firstly studied based on both VS and DS for dewatering. Optimal dosage of 107–110 mg Fe 2+ /g VS and 86–88 mg H2 O2 /g VS for different sludge. Optimal oxidation reagent dosages based on DS fluctuated for different sludge. Advance oxidation reagents mainly acted on LB-EPS of sludge flocs.